2019
DOI: 10.3390/ma12111823
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impact of Zinc Oxide Nanoparticles on Differentiation and Cytokine Secretion of Human Adipose-Derived Stromal Cells

Abstract: Zinc oxide nanoparticles (ZnO-NPs) are widely utilized, for example in manufacturing paints and in the cosmetic industry. In addition, there is raising interest in the application of NPs in stem cell research. However, cytotoxic, genotoxic and pro-inflammatory effects were shown for NPs. The aim of this study was to evaluate the impact of ZnO-NPs on cytokine secretion and differentiation properties of human adipose tissue-derived stromal cells (ASCs). Human ASCs were exposed to the subtoxic concentration of 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Information on the influence of IONPs exposition and their intracellular accumulation on the functional capabilities of hASCs is still incomplete and partially controversial [14,43,44]. Our study group previously demonstrated the intracellular accumulation and persistence of ZnO-NPs in hASCs after long-term cultivation [34,45]. Exposure of ZnO-NPs affected cell migration of hASCs [46], but not their ability to multidifferentiate [34,46].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Information on the influence of IONPs exposition and their intracellular accumulation on the functional capabilities of hASCs is still incomplete and partially controversial [14,43,44]. Our study group previously demonstrated the intracellular accumulation and persistence of ZnO-NPs in hASCs after long-term cultivation [34,45]. Exposure of ZnO-NPs affected cell migration of hASCs [46], but not their ability to multidifferentiate [34,46].…”
Section: Discussionmentioning
confidence: 66%
“…Our study group previously demonstrated the intracellular accumulation and persistence of ZnO-NPs in hASCs after long-term cultivation [34,45]. Exposure of ZnO-NPs affected cell migration of hASCs [46], but not their ability to multidifferentiate [34,46]. The present study was conducted to add information on the effect of citrate-coated VSOPs on hASCs.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…53 On the other hand, subtoxic concentrations of ZnO NPs did not affect cytokine secretion and differentiation of human adipose tissue-derived stromal cells. 54 Toxic effects on isolated mice bone marrow mesenchymal stem cells were observed with ZnO NPs of 6-8 nm in size, leading to mitochondrial and cytoskeletal disturbances and increased ROS generation at concentrations above 20 mg/mL. 55 The cytotoxicity of ZnO NPs is known to be dependent on their size.…”
Section: -mentioning
confidence: 99%
“…The ZnO-NP were previously characterized by our group [17,18]. Transmission electron microscopy (TEM) (Zeiss transmission electron microscope EM 900, Carl Zeiss, Oberkochen, Germany) was used to assess particle size distribution and morphology at the Division of Electron Microscopy at the Biocenter of University of Würzburg.…”
Section: Characterization Of Zno Nanoparticlesmentioning
confidence: 99%